Social Media as a Coping Tool Amongst Social Studies Pre-Service Teachers - Pedroso, John Erwin; Notes, Fides Anna; Ferrer, Mary Princess; Jardeleza, Leony Cris; Estuya, Christian Bryle; Empil, Bea Dyasenth (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Social media has many uses on a day-to-day basis, like being a coping tool that can be used in different coping strategies. This study aims to describe how Social Studies Pre-service Teachers use social media as a coping tool. A qualitative descriptive study that utilized an online semi-structured interview form to gather data from eight (8) Social Studies pre-service teachers through purposeful sampling with inclusion criteria. The information gathered from their responses were then analyzed using content analysis. Three themes emerged namely, problem-focused coping, emotion-focused coping and social coping and seven (7) categories. Likewise, seven meaningful categories that emerged were, Seeking Information, Outletting Expression, Sourcing Relief, Being Mindful of Emotions, Keeping in Touch with Loved Ones, Meeting New People Online and Collaborating with Classmates. Social media serves as a coping tool in various ways and previous studies show that social media may both be a positive and negative coping tool. Therefore, one must understand the categories of coping tools in the lens of social media to provide adequate emotional and social help, thus using social media for healthier usage.